Sapere ausus: Paweł Włodkowic w obronie praw narodów (ius gentium) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The main founders of the Cracow school of the law of nations, Paweł Włodkowic and Stanisław of Skarbimierz, in order to defend the Polish raison d’etat in the conflict with the Teutonic Knights, created a coherent and comprehensive system of international law, drawing on Western and indigenous legal and philosophical-theological traditions. Based on the principles of divine and natural law, combining law with morality and justice with truth, they defended the rights of all nations. As a point of support for their argumentation, they adopted the Christian concept of the dignity of man and his natural rights and the fundamental role of the God’s commandment of love in the life of individuals as well as societies. These universal, objective and immutable human rights include: the right to life and its protection, the right to liberty, the right to property and the right to a fair trial. And the fullest expression of the human law of nature is the ius gentium – the law of nations, as the reasonableness of man expresses itself most fully in society. The legal principles thus developed in defence of one’s freedom could serve as a model for the international bodies of the time and, in essence, are still relevant today.